PELATIHAN PENINGKATAN KAPASITAS GURU SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH SAYAP IBU BINTARO - Penny Handayani; Pradita Sibagariang; Gabriella Irena Carissa; Jessica Paramitha; Weny Pandia Sembiring (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Teachers have an important role in the running of educational activities in schools, both regular and special schools. The competence of teachers who teach will greatly determine the achievement of the learning goals given in the ongoing curriculum. With the limited human resources available in the area of children with special needs, there are times when teachers who teach do not have the minimum competence needed to make teaching and learning activities run smoothly, so learning targets become a challenge in itself. Teachers who teach in special schools should also have special competencies to be better prepared to handle and educate Students with Special Needs (SBK). This study used a mixed-method with a group discussion forum, interviews, and questionnaires to get a deeper picture of the competence of teachers at the Sayap Ibu Bintaro Foundation (YSIB). The results showed that there are internal and external factors that affect the competence of teachers at YSIB. Teacher knowledge and skills in behavior management, recognizing SBK characteristics, and communication with SBK still need further development. This results in the teacher's teaching strategy not optimal in their daily lives. Therefore, a form of intervention is needed to improve teacher competence, especially in behavior management, recognizing SBK characteristics, and communication skills with SBK. The intervention was carried out by training